Confidence-Building Measures in the Potential Conflict Management of the Arctic Region - M Dwiki Mahendra (Jurnal Studi Diplomasi dan Keamanan, 2022)
As the climate crisis occurs, the Arctic Region faces new opportunities and challenges due to the opening of water areas that were originally covered by a layer of ice. The opening of access to exploration and exploitation upon resources in the area encourages territorial disputes and puts the whole Arctic Region in potential danger of an open conflict. This had led the Arctic Region in need of disputes management efforts alongside the management of its conflict potential, this is due to the fact that this issue is involving actors with massive influence that could affect not only the Arctic Region but also the rest of the world. This article explains how territorial disputes and potential conflicts in the Arctic Region have been managed by actors in the region through a series of policies as part of the Confidence-Building Measures (CBMs). This study uses qualitative analysis through literature study to understand how the CBMs mechanism is implemented in the Arctic Region to assist the bilateral dispute resolution process.